The paradigm of self-care: an exploratory study of teacher perceptions for conserving and preserving oneself in the high-stress, people-intensive field of education - Marquez, Alexander D. (Kansas State University, 2023)
Teachers all around the world are finding their profession laden with substantial stress. Many are considering quitting, or at a minimum, finding themselves taking time off in order to cope with the pressures of the job. Teachers are over-burdened by low pay and heavy workloads: planning and grading, high expectations, performance evaluations, standards-based accountability and testing, extra-curricular duties, undisciplined students, unsupportive administrators, and angry parents. Many educators are wondering if these demands are even worth the sacrifice any longer. While teaching is incredibly rewarding, something has to give. Effective self-care (ESC) can provide the much-needed relief to not only survive but thrive in all areas of life. However, self-care is an elusive and relative term that is becoming an emerging topic of interest in the research world, particularly during and following the COVID-19 pandemic. This study explores the paradigm of self-care from the perspectives of 24 teachers to answer: 1) How do teachers conceptualize what self-care entails? 2) What self-care strategies, if any, do teachers believe are most effective? 3) To what extent do teachers feel they effectively engage in self-care? and 4) What contextual, personal, or economic factors enable or constrain teachers’ ability to engage in self-care? Utilizing an online survey and six one-on-one interviews, this mixed-methods study uncovered what teachers are experiencing in their daily lives: stress levels and demands are high, time is a rare commodity, being intentional with self-care is key, and healthy boundaries must be set in order to cope with the pressures of teaching and balance work and personal life. Furthermore, a construct based on research data was produced called the Teacher Conservation and Preservation Synergy Model© which demonstrates that exploring ESC for teachers is an essential and significant matter that should be kept at the forefront of our attention as we work to conserve and preserve education’s greatest resource: our teachers.
Keywords: Self-care; Teacher; Self-efficacy; Agency; Motivation; Retention; Absenteeism